2014
DOI: 10.1371/journal.pone.0087192
|View full text |Cite
|
Sign up to set email alerts
|

Supported Palladium Nanoparticles Synthesized by Living Plants as a Catalyst for Suzuki-Miyaura Reactions

Abstract: The metal accumulating ability of plants has previously been used to capture metal contaminants from the environment; however, the full potential of this process is yet to be realized. Herein, the first use of living plants to recover palladium and produce catalytically active palladium nanoparticles is reported. This process eliminates the necessity for nanoparticle extraction from the plant and reduces the number of production steps compared to traditional catalyst palladium on carbon. These heterogeneous pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 34 publications
1
81
1
Order By: Relevance
“…Some examples of plantsupported metal catalysts have been reported in the past ten years. 42 Compared with the Pd-P-300 catalyst, a marked increase of diameter and size distribution of Pd NPs was found in the Pd-P-800 catalyst, which was detrimental to the catalytic activity. Afterwards, Jia et al 292 reported the biosynthesis of Pd NPs supported by the biomass of Gardenia jasminoides Ellis that can serve as long lifetime nanocatalysts for p-nitrotoluene hydrogenation.…”
Section: Catalysismentioning
confidence: 97%
“…Some examples of plantsupported metal catalysts have been reported in the past ten years. 42 Compared with the Pd-P-300 catalyst, a marked increase of diameter and size distribution of Pd NPs was found in the Pd-P-800 catalyst, which was detrimental to the catalytic activity. Afterwards, Jia et al 292 reported the biosynthesis of Pd NPs supported by the biomass of Gardenia jasminoides Ellis that can serve as long lifetime nanocatalysts for p-nitrotoluene hydrogenation.…”
Section: Catalysismentioning
confidence: 97%
“…Subsequent TEM results visualised the PdNPs produced were at 2-4 nm size range. The produced PdNPs were subsequently used in Suzuki-Miyaura coupling reactions where the biogenic PdNPs were shown to convey a higher catalytic activity that commercially available PdNPs [74].…”
Section: Nanoparticle Synthesis By Plantsmentioning
confidence: 99%
“…Recently, palladium nanoparticles from Arabidopsis plant culture and K 2 PdCl 4 were prepared [38]. The reduction was complete in 24 h. TEM images of different sections of the plant showed well-dispersed spherical metallic nanoparticles of an average diameter of 3 nm during first 3 h. As the incubation time increased, the size and concentration of nanoparticles also increased up to 32 nm.…”
Section: Reviewmentioning
confidence: 99%